Challenges and opportunities in animal models of gambling-like behavior. (February 2020) - Vonder Haar, Cole
Highlights: Animal models are robust for investigating risk-based decision-making. Environmental factors are key to the development of decision-making patterns. Risk-based decision making can be used to investigate comorbid disorders. Abstract : In the past several years, there has been an explosion of interest in animal models of risk-based decision-making, a fundamental process associated with gambling disorder. While early work focused on establishing various tasks for assaying decision-making, current studies are determining the (subtle and not-so-subtle) influence of cues in driving risky decisions to better understand problem gambling. In addition, these decision-making paradigms are now being used to investigate comorbid conditions such as substance dependence or brain injury and replicating observations from human patients. These animal models have now developed to a point where therapeutic interventions may be assessed for not just gambling disorder, but also a number of other conditions which engender risky decision-making.